2014
DOI: 10.1021/ac503706n
|View full text |Cite
|
Sign up to set email alerts
|

Direct Ionization of Solid-Phase Microextraction Fibers for Quantitative Drug Bioanalysis: From Peripheral Circulation to Mass Spectrometry Detection

Abstract: A novel approach is described for the quantitative bioanalysis of drugs in blood samples by ionization of the analytes collected on solid-phase microextraction (SPME) fibers by mass spectrometry (MS). The technique combines the attractive features of SPME microsampling using minimal sample volumes with the speed, selectivity, and sensitivity capabilities of MS detection. The method reported in this study involved generating gas-phase ions directly from SPME fibers without the need for any additional sample pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
5

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 27 publications
0
43
0
5
Order By: Relevance
“…The same authors reported the use of coated-blade SPME devices, from which the analytes were electrosprayed [21]. Other approaches are based on SPME-DESI-MS [22] and solvent-assisted spray-based SPME-MS [23]. Recently, another SPME-LTP-MS coupling was reported [24].…”
Section: Introductionmentioning
confidence: 99%
“…The same authors reported the use of coated-blade SPME devices, from which the analytes were electrosprayed [21]. Other approaches are based on SPME-DESI-MS [22] and solvent-assisted spray-based SPME-MS [23]. Recently, another SPME-LTP-MS coupling was reported [24].…”
Section: Introductionmentioning
confidence: 99%
“…Ahmad et al. developed a method for the quantitative bioanalysis of two beta‐blockers, metoprolol and propranolol, in blood samples by inserting C18 fiber directly into the MS . In an attempt to mimic the intravenous blood flow in a living organism, the SPME fibers were exposed to blood samples with 500 rpm agitation.…”
Section: Spme In Biomedical and Clinical Studiesmentioning
confidence: 99%
“…Therefore, solid-phase micro-extraction (SPME) is used more and more frequently [121]. Because of the smaller sample volumes required and its reduced solvent consumption, lower cost and high-performance characteristics, SPME is also very suitable for the analysis of biological samples [51,122]. A detailed summary of key features of SPME, SPE and LLE can be found in Boyaci et al [123].…”
Section: (D) Sample Preparationmentioning
confidence: 99%